The Influence of Social Impact, and Product Quality on Sustainable Business Growth in the Textile Industry in Bandung - Thalib, Najdah; Nainggolan, Hotnida; Siregar, Fuad Gagarin; Firdaus, Gegga Firyant (Westscience Press, 2023)
Within the framework of Bandung's textile industry, this study explores the intricate relationships that exist between social effect, product quality, and sustainable economic success. The survey included a sample of 150 companies with a range of product specializations and sizes. Using partial least squares structural equation modeling, measurement model assessment, discriminant validity analysis, and structural model analysis were carried out (PLS-SEM). Product quality, social impact, and sustainable business growth were found to be significantly positively correlated. The results also confirmed discriminant validity among the latent constructs and showed strong reliability and validity of the measurement model. The suggested structural equation model's applicability is highlighted by the model fit evaluation. It can be shown from the R-Square and Adjusted R-Square values that the model can account for almost half of the variation in sustainable business growth. Future research directions are suggested, and implications for corporations and policy makers are examined.